Stylistics and Translation of Raymond Queneau’s Work: Translation Analysis of „Exercices de style“ - Černiuvienė, Liucija; Montrimaitė, Ieva (Vertimo studijos, 2020)
The article covers the stylistics of the work “Exercices de style” by the French writer Raymond Queneau and the translation of this work into Lithuanian. Through the analysis of translations into Italian and English as well, the article investigates the distinctive feature of Queneau’s texts – how they play with various language tools. The article distinguishes and discusses the play of literary devices (these are figures of style and rhetoric), the play of linguistic devices (grammatical tenses, barbarisms, neologisms), the play of language registers (colloquial language, jargon), the play of genres and discourses, and the play of narrative techniques. While playing with the language, the author seeks to entertain the reader – the exercises are rich in various elements of comedy, parody and irony. It is not possible to systematically apply one translation strategy to translate this work, therefore the translator Akvilė Melkūnaitė focused on conveying the logic of Queneau’s rules, making the translation strategies related to semantic and stylistic translation of the text diverse and successful, while the complicated conveying of cultural realia (e.g. jargon) is offset by other means of translation.
Keywords: literary translation; Raymond Queneau; Exercices de style; Stiliaus pratimai; language play